2012
DOI: 10.1093/eurjhf/hfs015
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in patients with decompensated heart failure: the Cognitive Impairment in Heart Failure (CogImpair‐HF) study

Abstract: AimsThe objective of this study was to examine cognitive and psychological processes systematically in patients with decompensated chronic heart failure (CHF) and to document changes in cognitive function after compensation. Executive functions, episodic memory, and attention are impaired in patients with stable CHF, influencing health behaviour and disease management. Cognitive function and psychological co-morbidities are associated with hospitalization, disability, and mortality. Methods and resultsCognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
3
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 43 publications
1
63
3
6
Order By: Relevance
“…Using a 1 h retention interval between training and testing phase, we could show that CHF mice display less habituation to the testing environment and a significantly decreased ability to discriminate between a novel and a familiar object. Thus, CHF induced deficits in short-term recognition memory, which is found in patients with depressive disorder (Kindermann et al, 2012). …”
Section: Discussionmentioning
confidence: 97%
“…Using a 1 h retention interval between training and testing phase, we could show that CHF mice display less habituation to the testing environment and a significantly decreased ability to discriminate between a novel and a familiar object. Thus, CHF induced deficits in short-term recognition memory, which is found in patients with depressive disorder (Kindermann et al, 2012). …”
Section: Discussionmentioning
confidence: 97%
“…Previous diagnosis of CILVEF ≤40%Multidomain neuropsychiatric battery58% of HF pts had CI with poor scores in the domains of verbal learning and verbal memoryBratzke-Bauer 2013 [29]47 HF-REFAge >50 years and ambulatory outpatients onlyHF-REF: 75 (9)Cross-sectionalHistory of HF >6 monthsCo-morbid psychiatric, neurological or physical illness. Previous diagnosis of CILVEFMultidomain neuropsychiatric battery23% of the HF-REF cohort showed evidence of CI33 HF-PEFHF-PEF: 68 (15)Stable on medication ≥4 weeksNYHA3% of the HF-PEF cohort showed evidence of CIHF-PEF based on AHA criteriaHuijts 2013 [30]491 HF-REFAge >60 years and ambulatory outpatients only77 (8)ProspectiveHF-REF: hospitalization within past yearCo-morbid physical illnessHF-REF: LVEF <45%, NYHA II-IV, NT-proBNP >400 pg/mlAMT8% of HF-REF group showed evidence of severe CI (AMT ≤7)120 HF-PEFHF-PEF: NT-proBNP ≥400 pg/ml if pt <75 years or ≥800 pg/ml if pt ≥75 yearsHF-PEF: LVEF ≥45%13% of HF-PEF group showed evidence of severe CI (AMT ≤7)Kindermann 2012 [31]20 decompensated HF ptsDecompensated HF: non-consecutive admissions to hospitalDecompensated HF: 60 (16)ProspectiveDecompensated HF: caused by ischaemic or DCM, symptomatic HF for ≥6 months, clinical signs of decompensation, for example, raised JVPCo-morbid psychiatric, neurological or physical illness. Previous diagnosis of CILVEF <45%Multidomain neuropsychiatric batteryDecompensated HF group scored lower than stable HF group in domains of memory, executive control and processing speed20 stable HF ptsStable HF: outpatientsStable HF: 61 (17)Stable HF pts: CHF of ischaemic or DCM, NYHA III-IV, no clinical signs/history of decompensation for ≥3 monthsNYHA III/IVStable HF group scored lower than the healthy control group in domains of intelligence and episodic memory20 healthy controlsHealthy controls: 62 (15)

AHA, American Heart Association; ALID, adjective list of Janke and Debus; AMT, Abbreviated Mental Test; BNP, brain natriuretic peptide; CAD, coronary artery disease; CHF, congestive heart failure; CI, cognitive impairment; CIMS, complex ideational material subset; CO, cardiac output; CV, cardiovascular; CVLT, California Verbal Learning Test; DCM, dilated cardiomyopathy; DRS, Disability Rating Scale; E/A ratio, ratio of mitral peak velocity of early filling (E) to mitral peak velocity of late filling (A); EF, ejection fraction; HF, heart failure; HF-REF, heart failure-reduced ejection fraction;...

…”
Section: Heart Failure and Cognitive Impairment – Strength Of Associamentioning
confidence: 99%
“…Decrease in body mass index after cardiac rehabilitation also predicts improved cognitive function in elderly patients with heart failure [162]. Cognitive function is significantly impaired in decompensated CHF compared to stable CHF patients, but it improves with the management of decompensated CHF [163]. Better adherence to treatment of heart failure has been shown to predict improved cognition [164].…”
Section: Cognitive Dysfunctionmentioning
confidence: 99%
“…More CHF patients are now living longer to older age, with more comorbidities and associated polypharmacy [163]. A study looking at drugs prescribed at discharge to patients hospitalized for CHF revealed the mean number of drugs was 6.8, representing 10.1 daily doses [164].…”
Section: Comorbidity and Polypharmacymentioning
confidence: 99%